Operating systems an introduction - Garg, R.; Verma, G. (Mercury Learning and Information, 2017)
This book is designed to provide a step-by-step approach to understanding basic concepts of operating systems. In addition to traditional operating systems like Windows, it covers the main features of Red Hat Linux, iOS, and Android systems. Useful as a textbook for an introductory course in operating systems or as a reference for industry professionals who need information on recent mobile operating systems.